The interrelations of green criminology and traditional criminology (Archives of Criminology, 2023)
Green criminology, whilst functioning under the banner of critical criminology since its inception, has slowly begun to have more and more to do with traditional criminology. The subject of this article is the interrelations of this new perspective and traditional considerations on crime. Green criminology seems to have much to offer mainstream criminology, enriching it with ideas that have hitherto been unnoticed or overlooked. In turn, the achievements of traditional criminology provide useful solutions and concepts that can enable green criminology to develop.